Clay Characterization and Bleaching of Crude Palm Oil Using Acid-Activated Nibo Clay - Nweke, Chinenyenwa N.; Ajemba, Regina O. (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2022)
Acid-activated Nibo clay was applied as an adsorbent in the bleaching of crude palm oil. The collected clay sample was activated with hydrochloric acid solution after it was sun-dried and ground. The raw (NC) and activated clay (ANC) samples were characterized using XRF, SEM, and FTIR analyses. The efficiency of the bleaching process was examined by varying the adsorbent dosage, temperature and the contact time. The results of XRF, SEM, and FTIR analyses on NC and ANC showed that the clays were kaolinites with significant changes after activation. The bleaching experiment showed that increase in temperature improved the efficiency of the process. The highest bleaching efficiency of 86% was observed. The pseudo-second-order model best described the adsorption process at 100 °C when compared to correlation coefficient values of the pseudo-first-order, Intra-particle diffusion and Elovich kinetic models. The Temkin isotherm model best fitted the experimental data than the Langmuir, Freundlich and Dubinin-Radushkevich models with R2 values of >0.9 at all temperatures. The enthalpy and entropy values were evaluated as 54,943.90 J/mol and 154.6321 J/mol respectively. The enthalpy and entropy values indicated that the adsorption process was endothermic and showed an increase in randomness at the solid/liquid interface. The negative values of the Gibb’s free energy at 363 and 373 K implied that beta carotene adsorption of crude palm oil at these temperatures was spontaneous and feasible. This experimental study showed that acid activated Nibo clay can be applied as an adsorbent for the bleaching of crude palm oil at higher temperatures.